From head orientation to hand control: evidence of both neck and vestibular involvement in hand drawing - Guerraz, Michel; Blouin, Jean; Vercher, Jean-Louis (Experimental brain research, 2003)
This research investigated the effect of head to trunk relation in a sensorimotor drawing task. In the first experiment, seated participants were asked to reproduce with eyes closed geometric shapes (square or diamond) with the tip of their right index finger in the frontoparallel plane. Their head was either aligned with the trunk or tilted 25 degrees towards the left or right shoulder. Results showed that drawings were subjected to an overall rotation of a few degrees in the opposite direction to the tilt. In two subsequent experiments, the respective contribution of both otoliths and neck receptors to this head tilt effect was investigated. In Experiment 2, seated participants kept their head straight but were subjected to 2.5 mA vestibular galvanic stimulation (GVS). Results indicated that GVS induced a small but significant deviation of the drawings towards the anode. Finally, in Experiment 3, subjects performed the drawing task either seated upright (seated condition) or lying on their back (supine condition). Unlike in the seated condition, tilting the head towards the shoulders in a supine posture does not modulate afferents from the otolith stimulation and therefore mainly stimulates neck receptors. Head tilt induced rotations of hand-drawn reproductions in both seated and supine conditions, suggesting a significant contribution of neck afferents in the control of hand motion in space in the absence of vision. Overall the data provided evidence for a strong head-hand linkage during kinaesthetically guided drawing movements.